Towards a quantum cascade laser-based implant for the continuous monitoring of glucose - Isensee, Katharina; Müller, Niklas; Pucci, Annemarie; Petrich, Wolfgang (The analyst, 2018)
Continuous glucose monitoring enables an improved disease management for people with diabetes. However, state-of-the-art, enzyme-based, minimally invasive sensors lose their sensitivity over time and have to be replaced periodically. Here, we present the in vitro investigation of a quantum cascade laser-based measurement scheme that conceptually should be applicable over elongated periods of time due to its reagent-free nature and may therefore be considered as an approach towards long-term implantation. The method uses a miniaturized optofluidic interface in transflection geometry to measure the characteristic mid-infrared absorption properties of glucose. A glucose sensitivity of 3.2 mg dL−1 is achieved in aqueous glucose solutions. While this sensitivity drops to 12 mg dL−1 in the presence of biologically plausible, maximum concentrations of other monosaccharides, it is still well within the medically acceptable range according to Parkes error grid analysis. With a response time of less than five minutes, our sensor should be able to react adequately fast to physiological changes in glucose concentration. Finally, no drift or deterioration was found during an extended, 42 days in vitro experiment. These results underline the potential of this technique for its conceivable applicability in vivo as a long-term glucose monitoring implant.